Kemampuan representasi matematis dan self-esteem siswa pada materi statistika - Ai Ristiani; Iyam Maryati (Institut Pendidikan Indonesia, 2022)
Mathematics is a part of science that can improve one’s ability to think logically, rationally, critically, carefully, effectively, and efficiently. The ability of mathematical representation is one of the general goals of learning mathematics in schools. Self-esteem is one of the aspects that determines the success of students’ interaction in the social environment, through self-image, learning process, experiences, and interaction in the social environment. The aim of this study was to analyze the students’ ability in mathematical representation and self-esteem in statistic material. This study was conducted in Kp. Babakan Manggung, RT/RW 03/06, Ds. Sukajaya, Kec. Tarogong Kidul with the subjects of this research is seven students in third grade in Junior High School IT Bani Adam Hawa and taken by randomly. The technics of conducting the data in this research are test, interview, questionnaire, and observation. The result of this study indicates that: (1) the student's ability to represent is still low. Of the seven students, only four students thought that the question related to pictures and mathematical models were not much difficult. (2) students’ self-esteem attitude is still classified as moderate because of the lack of students’ ability to instill confidence in themselves in communicating mathematics in their life. The students who have less self-esteem are very concerned with students' achievements (3) the students still have difficulty in learning mathematics because the students often forget the formula and are confused about how to work the questions. Matematika adalah salah satu bidang ilmu yang dapat meningkatkan kemampuan seseorang dalam berpikir secara logis, rasional, kritis, cermat, efektif dan efisien. Kemampuan representasi matematis merupakan salah satu tujuan umum dari pembelajaran matematika di sekolah. Self-esteem merupakan salah satu aspek yang menentukan keberhasilan siswa dalam berinteraksi dengan lingkungan sosial, melalui citra diri, proses belajar, pengalaman serta interaksi dengan lingkungan. Tujuan penelitian ini untuk menganalisis kemampuan representasi matematis dan self-esteem siswa pada materi statistika. Penelitian ini dilakukan di Kp. Babakan Manggung, RT/RW 03/06, Ds. Sukajaya, Kec. Tarogong Kidul dengan Subjek penelitian tujuh orang siswa SMP IT Bani Adam Hawa kelas IX yang diambil secara acak. Adapun teknik pengumpulan data dalam penelitian ini adalah tes, wawancara, angket, dan catatan lapangan. Hasil penelitian ini menunjukan bahwa : (1) Kemampuan representasi siswa masih tergolong rendah. Dari ketujuh responden hanya empat yang menganggap bahwa soal yang berkaitan dengan gambar, dan model matematika tidak terlalu sulit. (2) Sikap self-esteem siswa masih tergolong sedang karena masih kurangnya kemampuan siswa dalam menanamkan keyakinan terhadap dirinya dalam mengkomunikasikan matematika kedalam kehidupan sehari-hari. Siswa yang memiliki self-esteem kurang sangat mempengaruhi pada prestasi belajar lainnya. (3) Siswa masih mengalami kesulitan dalam belajar matematika karena siswa sering tiba-tiba lupa rumus serta bingung dalam langkah pengerjaan soal.